2006
DOI: 10.1007/bf03175025
|View full text |Cite
|
Sign up to set email alerts
|

The fungicidal efficacy of various commercial disinfectants used in the food industry

Abstract: The antifungal effects of eight commercial disinfectants namely alcohol, peracetic acid, iodophors, aldehydes, quaternary amine compounds (QAC, a, b and c), and a chlorine-based agent were assessed at different concentrations. The time taken for these disinfectants to kill different microorganisms was used to assess their efficacy. The microorganisms tested were six yeasts, Saccharomyces cerevisiae, Saccharomyces uvarum, Kloeckera apiculata, Candida oleophila, Metschnikowia fructicola, Schizosaccharomyces pomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…and Serratia marcescens, have exhibited high intrinsic resistance and survival after exposure to QACs [124][125][126][127]. Food-associated moulds and yeasts exhibit variable resistance among species and among strains within species; some isolates were resistant to typical QAC concentrations [128,129].…”
Section: Oral and Gastrointestinal Tract Microflora And Food-related mentioning
confidence: 99%
“…and Serratia marcescens, have exhibited high intrinsic resistance and survival after exposure to QACs [124][125][126][127]. Food-associated moulds and yeasts exhibit variable resistance among species and among strains within species; some isolates were resistant to typical QAC concentrations [128,129].…”
Section: Oral and Gastrointestinal Tract Microflora And Food-related mentioning
confidence: 99%
“…Nonetheless, fungal response to such cleaning agents varies with disinfectant type and concentration. For example, Korukluoglu et al [ 86 ] showed that Aspergillus niger was sensitive to alcohol but not to peracetic acid; moreover, A. niger was resistant to 0.5% iodophor but sensitive at 1%. In addition, Bundgaard-Nielsen and Nielsen (1995) demonstrated the existence of intraspecific variation in tolerance to quaternary ammonium compounds, especially in P. commune and Penicillium nalgiovense [ 87 ].…”
Section: Prevention and Control Of Fungal Spoilage In Dairy Producmentioning
confidence: 99%
“…9 Current approaches to avoid mold contamination usually involve the use of groups of chemicals such as fungicides and disinfectants, where disinfectants are typically alcohol-, peracetic acid-, iodophors-, aldehydes-, chlorine-, peroxygen-based, or a mixture of these chemicals. 10 For instance, a recently introduced and widely used liquid disinfectant known as Virkon is composed of a combination of oxone, sodium dodecylbenzenesulfonate and sulfamic acid plus various inorganic buffers. As a classical antimicrobial agent, it has a wide spectrum of disinfection activity, including effectiveness against fungal species.…”
Section: Introductionmentioning
confidence: 99%